2008
DOI: 10.1103/physreva.77.062321
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity approach to Gaussian transitions

Abstract: The fidelity approach to the Gaussian transitions in spin-one XXZ spin chains with three different values of Ising-like anisotropy lambda is analyzed by means of the density matrix renormalization group (DMRG) technique for systems of large sizes. We find that, despite the success in the cases of lambda=2.59 and 1, the fidelity susceptibility fails to detect the Gaussian transition for lambda=0.5. Thus our results demonstrate the limitation of the fidelity susceptibility in characterizing quantum phase transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
96
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 54 publications
17
96
1
Order By: Relevance
“…[10], and D c ∼ 0.97 in Ref. [26]. Among these works, only a single study [15] was based on the analysis of the string order, although data from the numerical-diagonalization calculations in this study for small clusters might not be sufficient to show the transition point.…”
Section: B Haldane-large-d Transition Linementioning
confidence: 99%
See 2 more Smart Citations
“…[10], and D c ∼ 0.97 in Ref. [26]. Among these works, only a single study [15] was based on the analysis of the string order, although data from the numerical-diagonalization calculations in this study for small clusters might not be sufficient to show the transition point.…”
Section: B Haldane-large-d Transition Linementioning
confidence: 99%
“…[9], in which the estimate of c gradually deviates from c = 1 around J z 1. In the report of Tzeng and Yang [26], the transition point and the …”
Section: Haldane-néel Transition Linementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand for marginal perturbations ∆ λ = d + z i.e., when one is moving along a manifold of critical points, the above scaling formula does not provide a definite prediction as both log-like terms and O(1) might appear. Accordingly moving along a line of gapless point may not give rise to a detectable fidelity drop [6,7].…”
mentioning
confidence: 99%
“…The lowest energy excitations of the D phase which reside in the S z r = ±1 sector, are gapped and consist of pairs of excitons and antiexcitons which can be bound. Numerical studies [45][46][47][48] have established that in the pure spin model the quantum critical point separating the D phase and Haldane phase occurs at D * /J c ∼ 0.96 − 0.971. It has been found that in a pure spin model such as the one discussed here, a quantum phase transition between the Haldane phase and the topologically trivial D phase is signaled by the change in sign of an inversion-symmetry-based order parameter [47] which is a nonlocal topological order parameter.…”
mentioning
confidence: 99%